Assessment of staphylococcus aureus colonization in bakery workers: a case study - Ribeiro, Edna (2018)
Human colonization by staphylococcus aureus is widespread among the community and is considered a high-risk factor for the development of clinical infections in either healthy or immunocompromised individuals. Human carriers become a bacterial reservoir with associated high risk to transfer the infection to others or contaminate foods and food surfaces during handling. The ingestion of staphylococcal enterotoxins present in food can lead to staphylococcal food poisoning (SFP) which can cause severe symptoms such as violent emesis, nausea, diarrhea, and prostration. Considering that food contamination by colonized food handlers represent a major risk for SFP, here we aim to assess S. aureus colonization prevalence of both sensible and resistant strains in a bakery as a case study. We report an elevated prevalence of S. aureus prevalence (40%) in bakery workers whereas 75% of identified strains were sensible to methicillin (MSSA) and 25% resistant (MRSA). This work raises awareness to the urge of creating valuable occupational health surveillance programs to avoid food contamination in the context of Public Health.